Mapeamento de cofatores SRC1, NCoR e REA nos testículos, dúctulos eferentes e próstata de ratos - Wiviane Alves de Assis (2018)
The male genital system is controlled by sex steroid hormones, among them androgens and estrogens. Their biological effects are mediated by the androgen (AR) and estrogen (ERα and ERβ) receptors, members of the nuclear receptor superfamily. These receptors alternate between states of activation and repression of transcription, depending on the presence or absence of hormone, respectively. Their transcriptional activities occur in association with corregulators proteins, which can be coactivators or correpressors the transcription process. These cofactors are members of the steroid receptor cofactor family (SRC), the nuclear receptor corepressor (NCoR) and repressor of estrogen receptor activity (REA) or prohibitin 2. The tissue-specific differences in the composition of cofactors are possibly responsible for the different responses of steroid receptors to ligands. Thus, the objective of this work was to evaluate and compare the cellular distribution of these cofactors in organs of the male genital system of rats, which have differential expression and/or coexpression of estrogen receptors ERα and ERβ. Using immunohistochemistry and immunofluorescence assays, we found that in the testes, Sertoli cells were positive for NCoR and REA and presented stage–dependent positivity for SRC1. Germ cells were positive for all cofactors, with stage- specific variation. During postnatal development and aging of the testes, REA’s subcellular localization was similar to ERβ’s and did not change with aging. In the efferent ductules, SRC1 and NCoR were expressed in ciliated and non-ciliated epithelium cells in all regions of this segment, as well as in smooth muscle cells and the surrounding connective tissue. In the prostate, SRC1 and NCoR were similarly expressed in epithelial and mesenchymal cells, being present in epithelial and stromal cells after cytodifferentiation. In summary, the differential expression of these cofactors in testicular cells, efferent ductules and prostate indicates that they can perform specific functions in these target organs, modulating transcriptional function by AR, ERα and/or ERβ. Our data provide evidence of differential distribution of these cofactors, which are not limited to androgen responsive cells, but there was a greater coincidence with ERβ expression, thus reinforcing a fundamental participation of estrogens in male reproduction.